2019
DOI: 10.1038/s41467-019-11590-2
|View full text |Cite
|
Sign up to set email alerts
|

Visualization and quantification of inhomogeneous and anisotropic magnetic fields by polarized neutron grating interferometry

Abstract: The intrinsic magnetic moment of a neutron, combined with its charge neutrality, is a unique property which allows the investigation of magnetic phenomena in matter. Here we present how the utilization of a cold polarized neutron beam in neutron grating interferometry enables the visualization and characterization of magnetic properties on a microscopic scale in macroscopic samples. The measured signal originates from the phase shift induced by the magnetic potential. Our method enables the detection of previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 48 publications
(48 reference statements)
0
11
0
Order By: Relevance
“…This lowers the contrast but increases equally the count rate. It has been calculated that the effective wavelength thus is 3.77 Å in this setup 55 . The effective wavelength resolution of the measurements can be assumed to be about , which coincides about with the step-width of our -scans in the subsequent sample measurements, and thus the resolution in these.…”
Section: Resultsmentioning
confidence: 79%
“…This lowers the contrast but increases equally the count rate. It has been calculated that the effective wavelength thus is 3.77 Å in this setup 55 . The effective wavelength resolution of the measurements can be assumed to be about , which coincides about with the step-width of our -scans in the subsequent sample measurements, and thus the resolution in these.…”
Section: Resultsmentioning
confidence: 79%
“…This interferometer produced various pioneering results of neutron phase imaging/tomography, showing that the dark-field signal (visibility reduction) is useful for depicting bulk magnetic domain structures [80][81][82] and superconductors [83]. Recently, its application has been extended to the visualization of magnetic fields by polarized neutron grating interferometry [84].…”
Section: Neutron-grating Fabricationmentioning
confidence: 99%
“…The peculiar feature of neutrons as charge neutral particles carrying a magnetic moment has been exploited in the study of magnetic phenomena [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. In neutron imaging, the interaction of the neutron magnetic moment with magnetic fields is exploited in various ways to image macroscopic magnetic fields and structural features [9,[18][19][20][21][22][23][24][25][26][27][28][29].…”
mentioning
confidence: 99%
“…Recently, we have shown that the use of a polarized neutron beam in a Talbot-Lau interferometer enables the characterization of strong magnetic fields through differential phase contrast imaging (DPCI) in cases where the incident spin couples adiabatically to the probed magnetic field [29]. Such an adiabatic transition takes place when ω L ≫ ðδB=jBjÞ=δt, where δB=jBj indicates the changes in direction of B [5].…”
mentioning
confidence: 99%